The interpretation of verbal and visual signs in education advertisements: submission of new university students - Komang Dian Puspita Candra; I Gusti Ayu Vina Widiadnya Puspita Putri (English, 2019)
The existence of advertisement cannot be separated from a verbal and nonverbal signs; this case also appeared in education advertisement, especially for submission new university student that used by the college as a form of promotion. A good advertisement will consider the use of verbal and nonverbal sign, so that, the prospective students understand the meaning of signs that will be transmitted by the advertiser. The common phenomenon is about the ability of people in understanding the advertisement. The prospective students sometimes difficult catch the meaning of the advertisement. This study is a semiotic research by using advertisement of submission new students in Indonesia as a data source. This study was conducted to find out the types of signs and the meaning behind the series of a sign who appeared in the advertisement, so that it can be known whether advertisement have used a sign in accordance or not. In an effort to data collection, observation with note taking technique was applied in methodology. Then data were analyzed qualitatively using the theory of semiotic by Barthes (1998), theory of meaning by Leech (1974) and several supporting theory such as theory from Leech (1966) about English Advertising, Pierce (2007) about the sign and images and theory proposed by Cazanave (2000) about the color. The data presented in the form of formal and non-formal. The results of the analysis found that these advertisements have been using a verbal and visual sign in well proportioned. Verbal sign consist of linguistic features such as the used of verb and adjective dominantly in lexical choice. There were four types of sentence structure found namely declarative, interrogative, imperative and exclamative sentence. It also used figurative language and abbreviation which has a correlation with the context. Besides the conceptual meaning to give information, from the sign there was also hidden message behind it. Visual sign consist of symbol, icon, index and color that make different reaction for every advertisement. These signs have important role in conveying the purposes of advertiser such as to persuade, command and give some information to public. It can be said that the use of verbal and visual aspects in these advertisement are in a right combination.